Interaction/cognition in design: The red bull station’s classroom case study - Trovo, Priscila; Valli, Adriana; Ferreira, Nivia; Carvalho, Agda [UNESP] (My University, 2017)
The present article aims at observing the possible interactions/cognitions of users, based on the activities and events that take place in the built spaces of a public building wherein educational, ludic, creative and experimental experiences occur. In this investigation, we will focus on the building that houses the Red Bull Station in São Paulo, Brazil, in particular the spatial arrangements of the Classroom, as they have been adapted to provide great flexibility for the artistic practices that are developed following the curatorial and projectual proposal. In the proposed study, the object of analysis are three situations that occur in the venue’s auditorium, which elicit and foster interactions and cognitions resulting from and rooted in a variety of content knowledge. The analysis of the aforementioned space is performed based on an understanding of the Classroom as a complex and fluid system, whereby the relations between the user and the built environment are alterable and articulated with the spatial configuration in which they occur. This condition foregrounds the great relevance of both the vision and the actual architectural design of the Classroom, as proposed by the Red Bull Station for the occupation/participation/experimentation of the user, whereby a crossover of educational, creative and cultural activities takes place. For this reason, the diversity of spatial arrangements provides a noteworthy experience, which stimulates and fosters open interactive engagements and encounters. The Red Bull Station’s proposal is articulated with a significant level of complexity, which allows for a constantly changing space, affording projectual flexibility to the project. Ultimately, this expands the possibilities for interaction and fosters a dynamic creative and cognitive process. As a result of the study, it can be observed that the Classroom’s projectual design provides much potential for interaction between the space and the user, and a high level of adaptability which enables a broad range of activities to be carried out.
Keywords: Classroom; Cognition; Design; Interaction; Spatial arrangements; Systemic complexity